Missing [videorecording (DVD)] - Merrick, Will; Johnson, Nicholas D.; Ohanian, Sev; Chaganty, Aneesh; Reid, Storm, 2003-; Almeida, Joaquim de, 1957-; Leung, Ken; Landecker, Amy, 1969-; Suri, Megan, 1999-; Griffin, Tim, 1969-; Henney, Daniel; Long, Nia (Sony Pictures Home Entertainment, 2023)
When the mother of a young woman goes missing with her boyfriend while vacationing in Columbia, she fears the worse. Although she is thousands of miles away, she uses everything in her power to get answers. After getting stonewalled and running into miles of international red tape, the young woman relies on her wit and savvy to find the answers. As time runs out, can she get the proof she needs to find her mother?